The Effect of Digital Visual Comic Media on Third-Grade Students' Reading Interest in Civic Education - Izzatul Nazwa Ussolehah; Diana Setiana; Asih Wahyuningsih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Reading interest plays a crucial role in improving elementary school students' learning achievement, particularly in Civic Education (PPKn). However, preliminary observations at SDN IV Dawuan revealed that most third-grade students demonstrated low reading interest due to the limited use of engaging instructional media. This study aimed to determine the effect of visual digital comic media on students' reading interest in Civic Education. A quantitative approach was employed using a pre-experimental method with a one-group pretest–posttest design. The study involved 39 third-grade students selected through saturated sampling. Data were collected using a reading interest questionnaire and analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-sample t-test. The findings showed a substantial improvement in students' reading interest after the implementation of visual digital comic media. The mean score increased from 37.08 in the pretest to 67.90 in the posttest, while the distribution of reading interest shifted from predominantly low (71.8%) before the intervention to predominantly high (69.2%) afterward. The normality test indicated that both datasets were normally distributed (pretest p = 0.051; posttest p = 0.099). Furthermore, the paired-sample t-test revealed a statistically significant difference between pretest and posttest scores (t = -10.090, p = 0.000 < 0.05), confirming that the implementation of visual digital comic media significantly improved students' reading interest. These findings suggest that visual digital comics provide an engaging and interactive learning experience that effectively promotes reading interest among elementary school students and can be utilized as an innovative instructional medium in Civic Education learning.